Measuring hospital case mix: Evaluation of alternative approaches for the Irish hospital system - Chris Aisbett; Miriam Wiley; Brian McCarthy; Aisling Mulligan (The Economic and Social Research Institute (ESRI), 2007)
The impetus for this study arose from the need to upgrade the case mix measure of choice in use at the national level in Ireland. Since 1993, various versions of the DRG grouper supported by the Health Care Financing Administration (HCFA) had been in use in Ireland. With improvements in available data, together with developments in the range and quality of alternative groupers available, it was considered timely to test performance of the alternative options on discharge abstract data for Irish hospitals. The groupers selected for testing included four versions of the Australian Refined (AR) DRGs, the AP DRGs (V18.0), CMS DRGs (V20) and IR DRGs (V1.2). Results for the HCFA DRGS (V16.0) were also included for purposes of comparison. The empirical analysis ranked the AR DRG Groupers highly relative to the alternatives. Additional factors favouring the AR DRG series of Groupers are the fact that they are the more widely used internationally, are updated regularly and supported by Australian government agencies. More support and training opportunities are also available for the use of these Groupers. Given these factors, together with the fact that the ICD-10-AM morbidity coding system is used in Ireland, the AR DRG classification system was recommended as the best option for use at the national level in Ireland.
Keywords: 330; case mix; DRG Groupers; AR DRGs; ICD-10-AM; Krankenhausfinanzierung; Betriebliche Budgetierung; Bewertung; Irland